Macro-anatomic, cross-sectional anatomic, and computerized tomographic examination of anal region in dogs - Cüneyt Tunahan Maviş; Memduh Gezici (Eurasian Journal of Veterinary Sciences)
Aim: The aim of the study is to examine the anatomical structures of anal region in dogs via different anatomical examination methods and to present an approach to the region in terms of three perspectives. Our study is important for presenting new approaches for the clinical cases such as perineal hernia, anal sac inflammation and fistulae, rectal prolapse etc. Materials and Methods: The study was conducted on 12 dog cadavers. Comparative dissection study was conducted on perineal region of 3 male and 3 female dog cadavers. A cross-sectional anatomical study was performed in 3 male and 3 female cadavers. From 1 male dog cadaver, computerized tomographic images of perineal region were obtained and added to the images obtained within the scope of the present study. Results: In the study, anal region was examined under three anatomical titles. Pelvic diaphragm and its anatomical structures, which are shown via figures and drawings in the literature, were determined using dissection, cross-sectional anatomy, and computerized tomography methods. Three-dimensional anatomical data obtained by sagittal, transversal and horizontal sections was comparatively determined via cross-sectional anatomy and computerized tomography methods. In addition, the values of the muscles of the anal region such as origin, insertion, thickness and width were measured and a correlation was found between the age of the dog and the measurements. Conclusion: The contribution of this study is important for development of diagnostic and treatment methods in approaches to be exhibited especially towards pathological and clinical cases such as perineal hernia, rectal prolapse, urethrotomy, anal sac inflammation and fistulae.